Political Economy of the Muslim Middle Class in Southeast Asia: Religious Expressions Trajectories in Indonesia, Malaysia and Thailand - Abdur Rozaki; Bayu Mitra A. Kusuma; Abd. Aziz Faiz (IKAT: The Indonesian Journal of Southeast Asian Studies, 2019)
The growth of Muslim middle class in the three Southeast Asian countries namely Indonesia, Malaysia and Thailand are heavily influenced by each state's political development policy as well as the growing phenomenon oftheMuslim market as part of the global market dynamics. This paper aims to describe the phenomenon of state and society relations in regardsto policies that influence the growth of the Muslim middle class and how the market contributes to their expansion. The research shows that Muslim middle class in Indonesia is a result of the ever-crisscrossing force between state-driven pro-market policies, market-driven mechanisms, and the development of information technology that creates the demands of modern lifestyles. In terms of the Malaysian context, the Muslim middle-class formation is closely linked toastate driven policy in the form of ethnicity-based policy: an affirmative policy to strengthen the Malays, which is identical with Islam. While for the case of Muslim middle class in Thailand, the formation is largely determined by the central government's political policy. The Thai government uses different political approaches, which varies depending on the level of the Muslim community’s compromise in each region. In the end, the differences in the process of Muslim middle-class formation in these countries shaped their Muslim communities’ religious expressionsboth economically and politically in the public sphere.